Variation in Infection Prevention Practices in Dialysis Facilities: Results From the National Opportunity to Improve Infection Control in ESRD (End-Stage Renal Disease) Project. (16th March 2015) - Chenoweth, Carol E.; Hines, Stephen C.; Hall, Kendall K.; Saran, Rajiv; Kalbfleisch, John D.; Spencer, Teri; Frank, Kelly M.; Carlson, Diane; Deane, Jan; Roys, Erik; Scholz, Natalie; Parrotte, Casey; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> OBJECTIVE To observe patient care across hemodialysis facilities enrolled in the National Opportunity to Improve Infection Control in ESRD (end-stage renal disease) (NOTICE) project in order to evaluate adherence to evidence-based practices aimed at prevention of infection. SETTING AND PARTICIPANTS Thirty-four hemodialysis facilities were randomly selected from among 772 facilities in 4 end-stage renal disease participating networks. Facility selection was stratified on dialysis organization affiliation, size, socioeconomic status, and urban/rural status. MEASUREMENTS Trained infection control evaluators used an infection control worksheet to observe 73 distinct infection control practices at the hemodialysis facilities, from October 1, 2011, through January 31, 2012. RESULTS There was considerable variation in infection control practices across enrolled facilities. Overall adherence to recommended practices was 68% (range, 45%–92%) across all facilities. Overall adherence to expected hand hygiene practice was 72% (range, 10%–100%). Compliance to hand hygiene before and after procedures was high; however, during procedures hand hygiene compliance averaged 58%. Use of chlorhexidine as the specific agent for exit site care was 19% overall but varied from 0% to 35% by facility type. The 8 checklists varied in the frequency of perfect performance from 0% for meeting every item on the checklist for disinfection practices to 22% on the arteriovenous access practices at initiation. CONCLUSIONS Our findings suggest that there are many areas for improvement in hand hygiene and other infection prevention practices in end-stage renal disease. These NOTICE project findings will help inform the development of a larger quality improvement initiative at dialysis facilities. Infect Control Hosp Epidemiol 2015;36(7):802–806